2016
DOI: 10.1039/c5ra26881h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of mixtures of NaA zeolite and sodalite from Ti-bearing electric arc furnace slag

Abstract: Ti-bearing electric arc furnace slag (Ti-bearing EAF slag) is the main solid waste generated in the direct reduction iron making process. During the extraction process of Ti from Ti-bearing EAF slag, a byproduct containing abundant Si and Al was seldom utilized, thus leading to waste of valuable elements and secondary pollution. In this paper, NaA zeolite (6Na 2 O$6Al 2 O 3 $12SiO 2 ) and sodalite (SOD, 4Na 2 O$3Al 2 O 3 $6SiO 2 ) were synthesized successfully using the by-product as a precursor. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…As shown in Figure 10, a well-crystallized 4A zeolite was formed when the reaction temperature was 60 °C. With an increase of temperature, the intensity of the diffraction peaks of hydroxysodalite gradually increased, which agrees with a similar result reported by Li et al [27]. Increasing the temperature to 90 °C caused the diffraction peaks of 4A zeolite to vanish, leaving only the diffraction peaks of hydroxysodalite, suggesting that relatively pure hydroxysodalite was prepared at this temperature.…”
Section: Effect Of Reaction Temperaturesupporting
confidence: 91%
“…As shown in Figure 10, a well-crystallized 4A zeolite was formed when the reaction temperature was 60 °C. With an increase of temperature, the intensity of the diffraction peaks of hydroxysodalite gradually increased, which agrees with a similar result reported by Li et al [27]. Increasing the temperature to 90 °C caused the diffraction peaks of 4A zeolite to vanish, leaving only the diffraction peaks of hydroxysodalite, suggesting that relatively pure hydroxysodalite was prepared at this temperature.…”
Section: Effect Of Reaction Temperaturesupporting
confidence: 91%
“…The photocatalytic activity increased with increasing Si/Al ratio. Due to the abundance of major constituent elements such Ti, Si and Al in slags, these studies clearly highlight novel approaches to the utilisation of otherwise problematic Ti-bearing steelmaking slags [134,135].…”
Section: Synthesis Of Zeolites From Slagsmentioning
confidence: 94%
“…To date, several studies have reported on the benefits of modification and/or activation treatment to increase the specific surface area and density of adsorption sites on the surfaces of the adsorbent particles [42,57,[59][60][61][62][63][64][65][66]. Other studies have also proposed the synthesis of functionalised adsorbents such as geopolymers [74,[118][119][120][121][122][123], permeable reactive barriers or slag filters [124][125][126][127][128][129][130][131][132], zeolites and zeolite precursors [133][134][135] and layered double-hydroxide-based adsorbents [133][134][135][136][137][138]. This section discusses in detail the opportunities to improve the adsorption capacity of slag-based adsorbents.…”
Section: Opportunities To Enhance the Adsorption Performance Of Slagsmentioning
confidence: 99%
See 1 more Smart Citation
“…Terzano et al utilized municipal glass and aluminium solid wastes for the preparation of NaA zeolite . Ti‐bearing electric arc furnace slag was used for the preparation of NaA zeolite . Maia et al reported the use of industrial kaolin waste for the preparation of zeolite A .…”
Section: Introductionmentioning
confidence: 99%